Solar Radiation Modification impact on precipitation and temperature extremes in Hunan, China - Haiyuan Tang; Mou Leong Tan; Zeqian Feng; Narimah Samat; Fei Zhang (Journal of Hydrology: Regional Studies)
Study region: Hunan Province, located in subtropical China, is highly susceptible to water-related disasters such as floods and droughts. Understanding localized impacts of climate intervention strategies is critical for hydro-climatic risk management and planning. Study focus: This study explores the potential impacts of Solar Radiation Modification (SRM) on extreme precipitation and temperature events in Hunan. Simulations from the GeoMIP6 project under SSP2–4.5 and SSP5–8.5, alongside SRM scenarios (G6solar and G6sulfur), are analyzed using bias-corrected outputs from four global climate models: CNRM-ESM2–1, IPSL-CM6A-LR, MPI-ESM1–2-LR, and UKESM1–0-LL. Quantile mapping was applied for bias correction using observed data as reference. Climate extreme indices recommended by the WMO were used to evaluate the extreme event changes. New hydrological insights for the region: The results show notable inter-model differences in simulating Hunan’s historical climate, particularly for precipitation and temperature extremes. Both SRM scenarios reduce heavy rainfall indices (Rx1day, Rx5day, R20mm), particularly after 2070, suggesting potential in flood risk mitigation. However, spatial patterns differ between G6solar and G6sulfur due to aerosol dispersion differences. Under SSP5–8.5, extreme temperatures are projected to rise significantly, while G6sulfur notably reduces cold nights. Conversely, consecutive dry days increase markedly under G6sulfur by 2080–2099, indicating limited drought alleviation. These findings highlight that although SRM may lower flood risks in subtropical areas like Hunan, its effectiveness in addressing drought remains limited.